Upaya Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran CTL Dengan Menggunakan Teknik Papercut Pada Pembelajaran Ragam Hias Di Kelas VII.2 SMP Negeri 1 Bambel Tahun Pelajaran 2020/2021 - Amrin (Journal of Technology and Literacy in Education, 2022)
This study aims to describe the improvement of student learning outcomes through the CTL gangan learning model using the papercut technique in decorative learning in class VII.2 SMP Negeri 1 Bambel in the 2020/2021 school year. This research was carried out where the researcher served as a teacher who taught arts and culture subjects, namely at SMP Negeri 1 Bambel, in the even semester of the 2020/2021 school year which was planned to be carried out for 3 months from January to March 2021. The subject of this research are VII.2 students of SMP Negeri 1 Bambel for the 2020/2021 academic year, totaling 26 students. This research is classroom action research. The data analysis technique used in this study was descriptive qualitative which was carried out using percentage calculations. The results showed that in the first cycle the average value of learning outcomes obtained was 66.15 with a percentage of completeness of 73.08%. While in the second cycle the average value of learning outcomes obtained was 73.85, an increase of 7.7 with a mastery percentage of 92.31% and an increase of 19.23%. An increase also occurred in teacher activities and student activities. In the first cycle the average teacher activity was 3.25 with sufficient criteria. While in the second cycle, the overall average was 4.5, which was in very good criteria and increased by 1.25. Student activity in the first cycle has a percentage of 66.67% and is in the sufficient criteria. While in the second cycle of student activity has a percentage of 88.33% and is in very good criteria. The increase experienced an increase of 22.16%. So it can be concluded that through the application of the CTL learning model using the papercut technique, it can improve student learning outcomes in decorative learning in class VII.2 SMP Negeri 1 Bambel in the 2020/2021 school year.